Towards an ecosystem approach to aquaculture: assessment of sustainable shellfish cultivation at different scales of space, time and complexity - Nunes, J. P. (2020)
The need for an ecosystem approach to aquaculture has led to the development of several aquaculture analysis tools in recent years, working at different scales of space (farm- to system-level), time (seasonal to annual and/or long-term analysis) and complexity (ease of use to complex process-based modelling). This work has tested the application of a range of complementary tools to the analysis of aquaculture practices and ecosystem impacts in Killary Harbour, Ireland. The selected tools included a system-scale, process based ecological model (EcoWin2000), a local-scale carrying capacity and environmental effects model (FARM) and a management-level eutrophication screening model (ASSETS). Both the system-scale and farm-scale models used ShellSIM to simulate individual shellfish growth. The tools were used to analyse the relationship between shellfish productivity and food sources, the impacts of changes to stocking densities of shellfish, and an overall assessment of the ecological status of Killary Harbour. EcoWin2000 was able to support a complex analysis, but required a significant amount of input data and effort for calibration and result analysis. FARM was able to provide similar (although less detailed) results at the shellfish farm scale with a smaller effort for parameterization and application, but was limited to testing scenarios with relatively moderate changes to present-day conditions. ASSETS provided simple, management-level results with a relatively low level of input data, although it is not appropriate for complex analysis. This paper illustrates the complementary nature of these tools, and how the unique capacities of each can be combined for integrated assessment of aquaculture in a coastal system. For Killary Harbour, the combined application of these tools revealed that: (i) the system's eutrophication status can be classified as Moderate Low, with a future trend of No Change; (ii) there is a large influence of ocean boundary conditions on shellfish food resources in the system; (iii) the maximum mussel production of the system is 4200 ton year− 1, but achieving this level would lead to lower harvest weights and longer growth cycles; and (iv) a scenario of lower stocking densities proposed for the system should lead to lower mussel productions, but could result in benefits such as higher mussel weight at harvest and/or shorter growth cycles.